THE EFFECTIVENESS OF GREEN COCONUT WATER (COCOS NUCIFERA LINN VAR. VIRIDIS) MOUTHWASH ON SALIVARY PH CHANGES IN 17-YEAR-OLD ADOLESCENTS - Abdi, Muhammad Jayadi; Anas, Risnayanti; Hasriana, Hasriana (Universitas Baiturrahmah, 2025)
Introduction: Dental caries is the most prevalent oral health problem faced by the Indonesian population. One of the primaryfactors influencing caries development is saliva. The acidity level of saliva plays a crucial role in enhancing the remineralization process of teeth. Green coconut water (Cocos nucifera Linn Var. Viridis) contains higher levels of tannins compared to other coconut varieties. Tannins exhibit antibacterial properties that can inhibit bacterial growth. However, the consumption of young coconut water can lower salivary pH due to its naturally low pH (5.5). The presence of acidic ions, such as vitamin C, total solids, lactic acid, and reducing sugars—including fructose, glucose, and amino acids— contributes to this effect.Aim: To determine the effectiveness of green coconut water (Cocos nucifera Linn Var. Viridis) gargling in altering salivary pH before and after use.Methods: This study employed a quasi-experimental design with a pre- and post-test control group approach. A total of 49 samples participated in the study. The subjects gargled with green coconut water, and their salivary pH was measured using a pH meter.Result: Statistical analysis using the Paired t-test showed a p-value of 0.00 (p<0.05), indicating a significant difference insalivary pH before and after gargling with green coconut water (Cocos nucifera Linn Var. Viridis).Conclusion: The findings of this study demonstrate a significant reduction in salivary pH after gargling with green coconut water (Cocos nucifera Linn Var. Viridis), suggesting its effectiveness in lowering salivary pH in 17-year-old adolescents.